Адаптивный потенциал интродуцированных сортов клевера лугового в Камчатском крае : ADAPTIVE POTENTIAL OF ALIEN VARIETIES OF MEADOW CLOVER IN KAMCHATSKY KRAI - Кочнева М. Б.; Дахно О. А. (Дальневосточный аграрный вестник, 2019)
В статье представлены результаты оценки 13 сортов клевера лугового по параметрам экологической пластичности, стабильности и адаптивности в суровых северных условиях Камчатского края. Исследования проводили в 2014-2018 годах на опытном поле ФГБНУ «Камчатский НИИСХ». Расчет показателей пластичности и стабильности проводили по методике Эберхарта и Рассела, в изложении В.А.Зыкина. Расчет коэффициента адаптивности осуществляли по методу Л. А. Животкова с соавторами. Объектом исследований являлись раннеспелые и позднеспелые сорта клевера лугового: Кудесник, Мартум, Кировский-159, Витязь, Орфей (НИИСХ Северо-Востока), СибНИИК-10, Атлант, Огонек (СибНИИ кормов), Смоленский-29, Делец (Смоленская СХОС), Гефест, Светлячок (НИИ Северного Зауралья), Командор (Приморский НИИСХ). Высокий потенциал урожайности в среднем за 5 лет пользования травостоем отмечен у раннеспелых сортов клевера Мартум (618 ц/га), Кудесник (555 ц/га), позднеспелых: Делец (623 ц/га), Светлячок (604 ц/га), Витязь (578 ц/га). На основе проведенного анализа к сортам интенсивного типа можно отнести сорта СибНИИК-10 (bi 1,2), Светлячок (bi 1,34). На основании коэффициента регрессии пластичными можно назвать раннеспелые сорта: Мартум (bi – 0,99), Кудесник (bi – 1,00), Смоленский-29 (bi – 0,94), Командор (bi – 1,14), позднеспелые сорта: Кировский-159 (bi – 0,90), Атлант (bi – 0,97), Огонек (bi – 1,01), Гефест (bi – 1,09) и Орфей (bi 1,14). Низкой экологической пластичностью отличались позднеспелые сорта Делец (bi – 0,60) и Витязь (bi 0,68). Высокой степенью адаптивности в конкретных условиях возделывания характеризуются сорта Делец, Мартум, Светлячок, Витязь, Орфей, Кудесник. Все изучаемые сорта клевера лугового отличаются в условиях Камчатского края нестабильным поведением (Si 2 – 99,47118,13-207,07). : The article presents the results of the assessment of 13 varieties of meadow clover using the parameters of ecological flexibility, sustainability and adaptability under the severe northern conditions of the Kamchatsky Krai. Investigations were carried out during 2014–2018 in the experimental field of the Kamchatka Research Institute of Agriculture. The calculation of indices of flexibility and sustainability was carried out according to the method of Eberhart and Rassell, as presented by V.A. Zykin. Calculation of the coefficient of adaptability was carried out by the method of L. A. Zhivotkov with co-authors. The object of the research was early ripening and late ripening varieties of meadow clover: Kudesnik, Martum, Kirovsky-159, Vityaz, Orpheus (Research Institute of Agriculture of the North-East), SibNIIK-10, Atlant, Ogonyok (Siberian Research Institute of Feed), Smolensky-29, Delets (Smolenskaya Agricultural Experimental Station), Hephaestus, Svetlyachok (Research Institute of Northern Zauralye), Komandor (Primorsky Research Institute of Agriculture). On average, high yield potential in 5 years of use of the grass stand was recorded in early ripening varieties of clover Martum (618 centners per hectare), Kudesnik (555 centners per hectare), late ripening varieties: Delets (623 centners per hectare), Svatlyachok (604 centners per hectare), Vityaz (578 kg / ha). On the basis of the analysis performed, varieties SibNIIK-10 (bi – 1,2), Svetlyachok (bi -1,34) can be attributed to varieties of intensive type. On the basis of the regression coefficient it is possible to consider the following early maturing varieties to be flexible: Martum (bi – 0,99), Kudesnik (bi – 1,00), Smolensky-29 (bi – 0,94), Comandor (bi – 1,14); flexible late ripening varieties: Kirovsky-159 (bi – 0,90), Atlas (bi – 0,97), Ogonyok (bi – 1,01), Hephaestus (bi – 1,09) and Orpheus (bi – 1,14). Late ripening varieties Delets (bi 0.60) and Vityaz (bi 0.68) showed low ecological flexibility. The varieties Delets, Martum, Svetlyachok, Vityaz, Orpheus and Kudesnik are characterized by a high degree of adaptability being under specific cultivation conditions. All the varieties of meadow clover under study show unstable behavior (Si2 – 99,47–118,13–207,07) under the conditions of the Kamchatsky Krai.